Some Biomechanical Determinants and Their Relationship to High Jumps Scoring Accuracy in Handball Players - Mohammad Majead Mohammed Saleh (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aimed to identify some of biomechanical determinants affecting accuracy of scoring from a high jump according to biomechanical variables in handball, as well as to verify value of correlation coefficient of these variables related to accuracy of scoring from a high jump in handball. Neglecting role of many biomechanical determinants and sometimes not referring to them, even though these determinants may have an effect, even if indirect, on direct variables affecting projectile. Research problem lies in knowing some of indirect variables and their effect on direct variables and knowing  priority in affecting scoring from a high jump, and this is a service to training process and thus achieving goals of scientific research. The researcher used descriptive method. Sample consisted of six players from Samarra University handball team, with a total of 72 observations. Sample was selected purposively based on their playing positions to achieve  study's objectives, as jump shot is a specialized skill. SPSS statistical package was used to analyze data, employing means, standard deviation, coefficient of variation, and Pearson's correlation coefficient. Results showed significant correlations between  studied variables and scoring accuracy. The researcher recommends designing training programs based on kinematic analysis to develop jump shot skill, and emphasizing these variables in training process.